Clinical profile and outcome of cardiomyopathies in infants and children seen at a tertiary centre. (15th January 2023) - Pagano, M.; Fumagalli, C.; Girolami, F.; Passantino, S.; Gozzini, A.; Brambilla, A.; Spinelli, V.; Morrone, A.; Procopio, E.; Pochiero, F.; Donati, M.A.; Olivotto, I.; et al.
Abstract: Introduction: Due to their rare prevalence and marked heterogeneity, pediatric cardiomyopathies (CMPs) are little known and scarcely reported. We report the etiology, clinical profile and outcome of a consecutive cohort of children diagnosed with CMP and followed at Meyer Children's Hospital over a decade. Patients and methods: We retrospectively reviewed patients consecutively referred from May 2008 to May 2019 for pediatric onset CMP (<18 years). Heart disease caused by arrhythmic disorders, toxic agents, rheumatic conditions and maternal disease were excluded. Results: We enrolled 110 patients (65 males), diagnosed at a median age of 27 [4–134] months; 35% had an infant onset (<1 year of age). A positive family history was more often associated with childhood-onset (38.8%). Hypertrophic cardiomyopathy (HCM; 48 patients) was the most frequent phenotype, followed by dilated cardiomyopathy (DCM; 35 patients). While metabolic and idiopathic etiologies were preponderant in infants, metabolic and sarcomeric diseases were most frequent in the childhood-onset group. Major adverse cardiac events (MACE) occurred in 31.8% of patients, including hospitalization for acute heart failure in 25.5% of patients, most commonly due to DCM. Overall, the most severe outcomes were documented in patients with metabolic diseases. Conclusions: In a consecutive cohort of pediatric patients with CMP, those with infantile onset and with a metabolic etiology had the worst prognosis. Overall, MACE occurred in 41% of the entire population, most commonly associated with DCM, inborn errors of metabolism and genetic syndromes. Systematic NGS genetic testing was critical for etiological diagnosis and management. Highlights: Children with CMP with infantile onset and with a metabolic etiology had the worst prognosis. MACE is most commonly associated with DCM, inborn errors of metabolism and genetic syndromes. NGS genetic testing was pivotal to reach an etiological diagnosis and guide management.